Mukena in Madurese Social Life - Mohammad Muslih; Muhtadi Abdul Mun'im; Khotimatul Mahbubah (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2021)
Mukena is a well-known typical dress for Indonesian Muslim women in conducting prayers. Mukena is taken for granted as a daily routine dress that did not receive much attention from many people in a more in-depth study, so it needed to be highlighted to the field of research. This study aims to determine two sides, namely, the meaning of dress in religious social life as well as to find out the meaning of mukena for Madurese. This study uses qualitative field research method. The sources of data are obtained from interviews and literature studies confined to things that only have relevance to this research. Using purposive sampling, the informants taken in this study were Madurese Muslim women from both santri and non-santri groups. The results discovered in this study are that Madurese Muslim women interpret clothes, including; as a part of social ethics, as a cover of aurat as well as an affirmation of social identity in a community. The meaning of mukena for Madurese Muslim women includes the following; mukena as a cultural tradition, as a form of self-sacralization, and as an affirmation of identity for Muslim women.